Multi-level regional development governance: A European typology - Cotella, Giancarlo; Janin Rivolin, Umberto; Pede, Elena; Pioletti, Maurizio (European Spatial Research and Policy, 2021)
The European Union identifies the regional level as the ideal spatial scale for resources’ redistribution, in so doing turning European regions into key spatial development players. This raises challenges due to the heterogeneity of the EU in terms of administrative configurations, and spatial governance and planning systems. The contribution of this article draws on the results of three interlinked ESPON research projects to shed light on the matter. Building on an overview of the institutional variables that may influence successful regional development, it proposes a typology of multi-level regional development governance in the EU and reflects upon the potentials for delivering economic, social, and territorial cohesion.